Handbook of seed technology for genebanks: Volume II: compendium of specific germination information and test recommendation - Ellis, R.H.; Hong, T.D.; Roberts, E.H.; International Board for Plant Genetic Resources (1985)
This second volume on seed technology for genebanks provides general approaches, detailed information, guidance and, when available, prescriptions for removing dormancy and germinating the seeds. It is the third in a general series of genebank handbooks. (Reprinted 1989)